Analysis of Internal and External Factors Influencing Rice Farmers’ Interest in Using Beauveria bassiana in Tirtomartani Village, Special Region of Yogyakarta: Analisis Faktor Internal dan Eksternal yang Memengaruhi Minat Petani Padi terhadap Penggunaan Beuaveria bassiana di Kalurahan Tirtomartani, Daerah Istimewa Yogyakarta - Satria Budi Kusuma; RR Siti Astuti; Rika Nalinda (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabaya, 2026)
This study analyzed internal and external factors influencing rice farmers' interest in using Beauveria bassiana to control Brown Planthoppers in Tirtomartani Village, Yogyakarta. A descriptive quantitative approach was used. The population consisted of 120 rice farmers, with a sample of 55 respondents selected using the Slovin formula and purposive sampling. Data were collected through observation, interviews, and questionnaires using a Likert scale, then analyzed using multiple linear regression. Results showed that farmers' interest in using Beauveria bassiana was high, with achievement scores of 85% for attention, 84.5% for interest, and 84% for involvement. Simultaneously, variables including age, education, farming experience, land area, extension intensity, and the role of farmer groups significantly influenced interest, with an R² value of 0.565 (meaning 56.5% of the variation in interest was explained by these variables). However, partially, only the role of farmer groups had a significant effect (p<0.05), while other variables showed no significant effect. These findings indicate that strengthening farmer groups as learning platforms and production units is important for increasing farmers' interest in adopting environmentally friendly pest control innovations.